THE PERFORMANCE OF EMERGING MARKETS MUTUAL FUNDS BEFORE, DURING AND AFTER MARKET DOWNTURNS - Hanchu, ZHANG (My University, 2016)
Investing in emerging market has been a trend among investors for many years, and for investors in developed countries, mutual funds have been one of the most important vehicles for them to make investment in emerging markets. In this paper, multiple liner regression is used to investigate the performance of US-based mutual funds investing in different emerging markets before, during and after the 2008 global financial crisis. The result of the paper is consistent with most of the previous literature conducting in this area. Emerging market mutual funds based in developed markets underperform their corresponding emerging market indices during the whole sample period and most of the sub-periods. Besides, funds with geographical focus yield better return than funds without geographical focuses. In addition, referring to the Morningstar fund rating methodology, data set is sorted into different portfolios according to the star rating. The regression result shows that mutual funds with higher star rating perform better than funds with lower star rating, and especially during the market recovering period, 5 star portfolio obtains positive and significant Jensen’s alpha.
Keywords: mutual fund; emerging market; financial crisis; Morningstar; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|